MiR‐542‐3p exerts tumor suppressive functions in neuroblastoma by downregulating Survivin. Issue 6 (5th August 2014) - Althoff, Kristina; Lindner, Sven; Odersky, Andrea; Mestdagh, Pieter; Beckers, Anneleen; Karczewski, Sarah; Molenaar, Jan J.; Bohrer, Anna; Knauer, Shirley; Speleman, Frank; Epple, Matthias; Kozlova, Diana; et al.
<x xml:space="preserve">Abstract</x> MicroRNAs (miRNAs) are deregulated in a variety of human cancers, including neuroblastoma, the most common extracranial tumor of childhood. We previously reported a signature of 42 miRNAs to be highly predictive of neuroblastoma outcome. One miRNA in this signature, miR‐542, was downregulated in tumors from patients with adverse outcome. Reanalysis of quantitative PCR and next‐generation sequencing transcript data revealed that miR‐542‐5p as well as miR‐542‐3p expression is inversely correlated with poor prognosis in neuroblastoma patients. We, therefore, analyzed the function of miR‐542 in neuroblastoma tumor biology. Ectopic expression of miR‐542‐3p in neuroblastoma cell lines reduced cell viability and proliferation, induced apoptosis and downregulated Survivin. Survivin expression was also inversely correlated with miR‐542‐3p expression in primary neuroblastomas. Reporter assays confirmed that miR‐542‐3p directly targeted Survivin. Downregulating Survivin using siRNA copied the phenotype of miR‐542‐3p expression in neuroblastoma cell lines, while cDNA‐mediated ectopic expression of Survivin partially rescued the phenotype induced by miR‐542‐3p expression. Treating nude mice bearing neuroblastoma xenografts with miR‐542‐3p‐loaded nanoparticles repressed Survivin expression, decreased cell proliferation and induced apoptosis in the respective xenograft tumors. We conclude that miR‐542‐3p exerts its tumor suppressive function in neuroblastoma, at least in part, by targeting Survivin. Expression of miR‐542‐3p could be a promising therapeutic strategy for treating aggressive neuroblastoma.